KEMAMPUAN PENGUASAAN DAN KETEPATAN PENGUCAPAN KOSAKATA BAHASA INGGRIS MAHASISWA JURUSAN PG PAUD FIP UNP - Rismareni Pransiska (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
This article reports on a research aimed at knowing the students ability in mastering English vocabulary and their pronunciation accuracy. The subjects were the students of PGPAUD FIP UNP who took part in Metododogi Pengenalan Bahasa Ingggris AUD class in 2011. This research employed descriptive quantitative method. The result showed that the ability of the students in mastering vacabulary was quite satisfied. However, the accuracy of pronounce was unsatisfied because many students cannot pronounce the word appropriately. Therefore they need to improve the pronunciations since they will introduce English vocabulary to kindergarten students later on.